Three-dimensional model of normal human dermal tissue using serial tissue sections - Liu, Peng; Zhang, Tao; Huang, Yihui (Frontiers in Bioengineering and Biotechnology, 2024)
Background: This study aims to construct a three-dimensional model of skin dermis utilizing continuous tissue sections, with the primary objective of obtaining anatomical structure data for normal human dermal tissues.Methods: Normal skin tissue specimens were acquired, paraffin-embedded, and subjected to HE staining. Panoramic images of skin sections were captured using a microscope. Tissue section images were aligned using the SIFT and StackReg image alignment methods, with analysis conducted using the OpenCV module. The mimics17 software facilitated the reconstruction of the skin dermal 3D model, enabling the calculation of dermal porosity and void diameter. Results: Panoramic skin slices exhibited high-resolution differentiation of dermal fibers and cellular structures. Both SIFT and StackReg image alignment methods yielded similar results, though the SIFT method demonstrated greater robustness. Successful reconstruction of the three-dimensional dermal structure was achieved.Quantitative analysis revealed a dermal porosity of (18.96±4.41)% and an average pore diameter of (219.29±34.27)μm. Interestingly, the porosity of the dermis exhibited a gradual increase from the papillary layer to the 4th layer, followed by a transient decrease and then a gradual increase. The distribution of mean pore diameter mirrored the pattern observed in porosity distribution. Conclusion: Utilizing the continuous skin tissue slice reconstruction technique, this study successfully reconstructed a high-precision three-dimensional tissue structure of the skin. The quantitative analysis of dermal tissue porosity and average pore diameter provides a standardized dataset for the development of biomimetic tissue-engineered skin.